CANINE PSYCHIATRY: THE IMPORTANCE OF APPROACHES TO ANIMAL PSYCHOPATHOLOGIES - Gil Dutra Furtado; Darla Barboza Da Silva; Felipe Eduardo da Silva Sobral (Environmental Smoke, 2022)
Animals exhibit analogous behavioral conditions that are equivalent to certain human psychiatric illnesses. Animal psychiatry is a growing field as more information about animals is uncovered, such as their ability to understand and interact with their guardians as well as their environment. The most commonly reported psychiatric disorders in companion animals such as dogs and cats are generalized anxiety disorder, obsessive-compulsive disorder, separation anxiety disorder, and post-traumatic stress disorder. The behavioral disorders of animals have great similarity with human psychiatry (such as generalized anxiety disorder, obsessive-compulsive disorder, impulse control disorders and panic disorder), and thus, models developed through scientific work with animals, may help in the understanding of human psychiatry, increasing the importance of veterinary psychiatric actions, bringing elucidations for the behavioral pathologies of pets and providing elements of the scientific basis for the advancement of human psychiatric actions. Problem behaviors are often the result of how an animal manages to interconnect specific factors such as how they reflect, how they feel, the genetic influence of each individual, and the environmental influences to which they are exposed. By taking these aspects into account and moving away from only direct description diagnoses of pathologies, and focusing on emotional and cognitive causes, we can diagnose, treat, and manage behavioral pathologies in pets, as well as generate valuable information for the many areas of psychiatric practice. The veterinary psychiatrist must evaluate physical disorders that may lead to or exacerbate abnormal behaviors so that these are not mistakenly dismissed. From there, noting the patients' ethological changes, the focus should shift to mental and emotional health, ranging from an assessment of normal behavior to the diagnosis of mental and emotional disorders, addressing emotions of anxiety and frustration, as well as other disorders. For each of these situations, actions such as behavior modification, management of the animal's environment, training, and, when necessary, use of medication, are methodologies that the Pv professional can and should use to seek to maintain the patient's well-being. The owner's concerns should never be overlooked, including management problems, aggression, affective disorder, elimination disorder, abnormal and repetitive behaviors, and ageing-related problems. In all these cases, help should be offered to the guardians with theoretical and practical actions focused on normal and abnormal behavior in dogs and cats from the point of view of emotion and cognition; provides protocols for behavior modification, doses and indications of drugs, in order to assist in the management of the case.